Effects of Nutrition Education Based on Social Cognitive Theory on Fruit and Vegetable Consumption Among Adolescent Girls in Tanakeke Islands, South Sulawesi - Firdaus, M Bambang Uswatul; Hidayanty, Healthy; Syam, Aminuddin; Hadju, Veni; Indriasari, Rahayu; Riskiyani, Shanti (Malaysian Journal of Medical Sciences, 2025)
Background: Indonesia, as an archipelagic country with a vast population, faces persistent challenges of undernutrition, particularly among adolescent girls, which impedes progress toward achieving the Sustainable Development Goals (SDGs). One key issue is inadequate intake of fruits and vegetables (FV). This study aimed to assess the effectiveness of nutrition education (NE) based on the social cognitive theory (SCT) in improving FV consumption among undernourished adolescent girls in the Tanakeke Islands, South Sulawesi, Indonesia. Methods: A quasi-experimental study through anthropometric and dietary assessments was conducted across four schools. The 12-week NE programme included role-playing exercises, educational modules for students, and monthly parental education sessions. Data were analysed using Statistical Package for the Social Sciences (SPSS) version 28, applying chi-square tests, independent t-tests, and paired t-tests, and analysis was conducted using repeated measures ANOVA with a significance level set at 0.05. Results: A total of 88 adolescent girls completed the study. Results showed significant improvements in the intervention group’s knowledge, outcome expectations, self-regulation, and FV consumption (P < 0.05). However, no significant change was observed in self-efficacy (P = 0.749). Conclusion: The research shows NE based on SCT, combined with parental involvement, effectively increases FV consumption among undernourished adolescent girls in remote, low-resource areas to improve adolescent nutrition. The lack of improvement in self-efficacy highlights the need for programme refinement to address this construct explicitly.